2023
DOI: 10.1002/acm2.13980
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the combination of intratumoral and peritumoral radiomic signatures for predicting epidermal growth factor receptor mutation in lung adenocarcinoma

Abstract: Purpose We investigated optimal peritumoral size and constructed predictive models for epidermal growth factor receptor (EGFR) mutation. Methods A total of 164 patients with lung adenocarcinoma were retrospectively analyzed. Radiomic signatures for the intratumoral region and combinations of intratumoral and peritumoral regions (3, 5, and 7 mm) from computed tomography images were extracted using analysis of variance and least absolute shrinkage. The optimal peritumoral region was determined by radiomics score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A recent study compared radiomic features of multiple peritumoral regions (3 mm, 5 mm, 7 mm) and constructed three machine learning models to predict EGFR mutation status in NSCLC. The results showed that combining intratumoral and peritumoral 3 mm radiomic features could better distinguish EGFR+ from EGFR− groups than 5 mm and 7 mm (training, p = 0.0000, test, p = 0.0025), but this study included only 164 patients and did not validate models with an external dataset [23]. Based on this, we expanded VOI_I outwards by 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 10 mm, and 15 mm to identify seven peritumoral regions and combined them with intratumoral regions to generate seven intratumoral and peritumoral regions, respectively, to compare the complementary value of different peritumoral regions to the predictive performance of radiomic models.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study compared radiomic features of multiple peritumoral regions (3 mm, 5 mm, 7 mm) and constructed three machine learning models to predict EGFR mutation status in NSCLC. The results showed that combining intratumoral and peritumoral 3 mm radiomic features could better distinguish EGFR+ from EGFR− groups than 5 mm and 7 mm (training, p = 0.0000, test, p = 0.0025), but this study included only 164 patients and did not validate models with an external dataset [23]. Based on this, we expanded VOI_I outwards by 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 10 mm, and 15 mm to identify seven peritumoral regions and combined them with intratumoral regions to generate seven intratumoral and peritumoral regions, respectively, to compare the complementary value of different peritumoral regions to the predictive performance of radiomic models.…”
Section: Discussionmentioning
confidence: 94%
“…Currently, several studies revealed that the radiomics model of the +3 mm peritumoral area effectively predicted chemotherapy response or EGFR mutation in non-small-cell lung cancer ( 19 , 29 , 30 ). This study of differentiating LPA and Non-LPA lung cancer also obtained the same peritumoral area (the PTV 0~+3 model had the best AUC in peritumoral models).…”
Section: Discussionmentioning
confidence: 99%